Assistance to Asturian miners : memorandum of interview, with representatives of the Mineworkers' Federation of Great Britain and Mr. W. Schevenels - Jones, J. ; Edwards, Ebby ; Lawther, W. ; Hall, S. ; Watson, Mr. ; Horner, Mr. ; Schevenels, Walther, b. 1894 ; Citrine, Walter, 1887-1983; Tewson, Vincent
1938-07-06 030-0122-002 292/946/30/122(ii)